2008
DOI: 10.1093/bja/aen184
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intra-articular dexmedetomidine on postoperative analgesia after arthroscopic knee surgery

Abstract: Intra-articular dexmedetomidine enhanced postoperative analgesia after arthroscopic knee surgery, with an increased time to first analgesic request and a decreased need for postoperative analgesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
82
1
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(88 citation statements)
references
References 18 publications
(12 reference statements)
3
82
1
2
Order By: Relevance
“…Al-Metwalli et al compared three groups using intra-articular dexmedetomidine, intravenous dexmedetomidine and placebo and concluded that intra-articular dexmedetomidine in a dose of 1 µg /kg enhanced postoperative pain relief and also reduced the need for postoperative analgesia and prolonged the time to first analgesic request. [9] These results are in agreement with our study. Our study was supported by the study by Das et al Das et al found that intra-articular levobupivacaine increases the duration of analgesia and decreases the need for rescue analgesic in first postoperative 24 hrs.…”
Section: Resultssupporting
confidence: 94%
“…Al-Metwalli et al compared three groups using intra-articular dexmedetomidine, intravenous dexmedetomidine and placebo and concluded that intra-articular dexmedetomidine in a dose of 1 µg /kg enhanced postoperative pain relief and also reduced the need for postoperative analgesia and prolonged the time to first analgesic request. [9] These results are in agreement with our study. Our study was supported by the study by Das et al Das et al found that intra-articular levobupivacaine increases the duration of analgesia and decreases the need for rescue analgesic in first postoperative 24 hrs.…”
Section: Resultssupporting
confidence: 94%
“…Intraarticular dexmedetomidine in patients undergoing arthroscopic knee surgery improves the quality and duration of postoperative analgesia [29,30].…”
Section: Intraarticular Usementioning
confidence: 99%
“…Peripheral nerve blocks or central blocks [6,7], and not long ago, intra-articular injection of various local anesthetic agents has become popular in clinical practice [2]. Drugs such as ketorolac, α2-agonists [8], opioids [3,9], and local anesthetics [10,11] have been tried to interrupt the pain pathway. Usage of these drugs in combination, called as the multimodal approach, is usually sufficient for providing analgesia in the initial post-operative period [12].…”
Section: Introductionmentioning
confidence: 99%
“…Intra-articular route of drug administration is an example for the management of pain after joint surgery utilizing the peripheral receptors [3]. Different authors in their previous studies with intraarticular ropivacaine [1,15], fentanyl [16], dexmedetomidine [11], levobupivacaine, and morphine [17] proved their efficacy in providing post-operative analgesia.…”
Section: Introductionmentioning
confidence: 99%